The effectiveness of radiotherapy and transarterial embolization for advanced gastric cancer bleeding - Yuki Ushimaru; Ryohei Kawabata; Kazuhiro Nishikawa; Tomohira Takeoka; Hiroshi Ikeda; Yutaka Kimura; Junya Fujita; Yoichi Makari; Akihiro Kitagawa; Nobuyoshi Ohara; Hideo Tomihara; Sakae Maeda; et al. (BMC Gastroenterology)
Abstract Background Advanced gastric cancer frequently leads to severe complications, such as bleeding, which severely impacts patients' quality of life and prognosis. Traditional approaches for hemostasis include endoscopic treatments and surgery, but their invasive nature and potential for significant morbidity have made less invasive options like radiation therapy (RT) and transarterial embolization (TAE) appealing. Nonetheless, studies comparing the therapeutic effects and prognosis of RT and TAE are limited, underscoring a significant gap in research and clinical practice. Methods This retrospective study analyzed patients with advanced gastric cancer who experienced uncontrollable bleeding and were treated with RT or TAE. The efficacy of these treatments was assessed based on the achievement of hemostasis, defined as the absence of the need for blood transfusion within 14 days post-treatment and no requirement for additional intervention for bleeding. Furthermore, the study evaluated the post-treatment course, including survival outcomes and re-bleeding rates, to compare the prognostic implications of treatment success or failure. Results This study encompassed 28 patients, of whom 19 underwent RT and 9 received TAE. RT was associated with a superior rate of immediate hemostasis (94.7% versus 66.7%, p = 0.047). Nonetheless, the incidence of re-bleeding in the RT cohort was 15.8%, compared to 44.4% in the TAE group, a difference that did not reach statistical significance (p = 0.11). Furthermore, the occurrence of adverse events was comparable between the two treatment modalities (21.1% for RT versus 33.3% for TAE, p = 0.48). An examination of long-term outcomes underscored the initial treatment's effectiveness and the potential transition to additional therapies as critical determinants of the re-bleeding risk. Groups achieving favorable initial outcomes (p < 0.001) and those for whom subsequent interventions were viable (p = 0.014) demonstrated a significant enhancement in re-bleeding-free survival. Despite the discrepancy in rates of immediate hemostasis, the comparison between the RT and TAE groups revealed no statistically significant difference in re-bleeding-free survival (p = 0.55). Conclusion RT exhibited superior hemostasis in advanced gastric cancer bleeding compared to TAE, yet both treatments showed similar re-bleeding-free survival rates. The success of the initial treatment, along with potential for further interventions, critically influenced outcomes, emphasizing the importance of effective initial hemostasis.